Professional Considerations for Audit Risk in Creating Smart Governance in Indonesia - Made Sudarma; Lely Kumalawati (Australasian Accounting, Business and Finance Journal, 2022)
This study aims to determine how different audit considerations determine risk between certified auditors and non-certified auditors. This study uses an empirical study approach using an experimental method. Experiments without control (natural) are carried out through audit cases encountered in the field during the audit process. This study's participants were 52 auditors with two categories, namely 26 participants with certified auditors and 26 participants for non-certified auditors. Data collection using the deployment of instruments after the field audit process is carried out. Based on the one-way analysis of the Annova test data, it shows that there are significant differences in audit considerations in determining risk between certified auditors and non-certified auditors. Certified auditors have more professional competence in providing audit considerations in determining risk. The problem of work culture for uncertified auditors is a residual risk that is difficult to detect and can lead to audit failure. Professional certified auditors' competence in providing risk considerations will encourage the formation of smart governance, given that auditors are a synergistic catalyst in organizational processes. Practical recommendations to the leadership of a government institution, especially state universities in Indonesia, that the internal auditors in a university, together with the leadership and the authorized departments, need to establish a risk map in a university leadership provision auditors. To always improve competence in the form of expertise certification training in the audit field. Professional judgment in determining audit risk by looking deeper into the theory of judgment decision making (Connolly, Arkes, and Hammond, 2000). The research approach used a study conducted by Fukukawa and Mock (2011). This study uses internal auditors at state universities in Indonesia, where an experiment is designed to determine internal audit risk. The determination of audit risk will ensure that the audit is right on target, effective, and efficient.
Keywords: professional auditor judgment; risk; internal audit